The Role of the Principal's Transformational Leadership in Improving Organizational Effectiveness at Sukarajakulon I State Elementary School - Supardi, Pardi; Saroni , M.; Araniri , Nuruddin (Al-Ilmu, 2024)
This study aims to analyze the role of the principal's transformational leadership in improving organizational effectiveness at Sukarajakulon I Public Elementary School. This research approach is mixed-method, with data collection through questionnaires, interviews, and observations. The results show that the transformational leadership style implemented by the principal has a significant influence on organizational effectiveness, especially in aspects of teacher work motivation, learning innovation, and collaborative work culture. These findings provide important implications for improving the quality of elementary school management.